Studies on the treatment efficiency of sediment phosphorus with a combined technology of PCFM and submerged macrophytes. (November 2015) - Zhang, Yi; He, Feng; Xia, Shibin; Zhou, Qiaohong; Wu, Zhenbin
Abstract: The removal efficiency of sediment phosphorus (P) in all fractions with a combined technology of porous ceramic filter media (PCFM) and submerged macrophytes was studied in Donghu Lake, Wuhan, China. The adsorption kinetic models of the sediment P in all fractions on PCFM could be described well by a power function equations (Qt = k · t a, 0 < a < 1). The P removal capacity of the combination of PCFM and Potamogeton crispus, a submerged macrophyte, was higher for all P forms than that of the combination of PCFM and another macrophyte, Vallisneria spiralis . This study suggested that the combination of PCFM and macrophytes could achieve a synergetic sediment P removal because the removal rates of the combinations were higher than the sum of that of PCFM and macrophytes used separately. The combined technology could be further applied to treat internal P loading in eutrophic waters. Graphical abstract: Highlights: PCFM were tested as novel sorbents for sediment P in all fractions removal. Adsorption kinetic models of sediment P on PCFM could be described by power function equations. Combination of PCFM and macrophytes could achieve a synergetic sediment P removal. Combined technology could be further applied to treat internal P loading in eutrophic waters. Abstract : The combination of PCFM and macrophytes could achieve a synergetic sediment P removal because the removal rates of the combinations were higher than the sum of that used separately.